2009
DOI: 10.1590/s0037-86822009000500011
|View full text |Cite
|
Sign up to set email alerts
|

A epidemia de aids no Estado de São Paulo: uma aplicação do modelo espaço-temporal bayesiano completo

Abstract: The State of São Paulo accounts for approximately 40% of the AIDS cases notified in Brazil and provides a suitable opportunity for space-time analysis aimed at better understanding of the dissemination of HIV/AIDS. Using the AIDS cases notified to the Ministry of Health between 1990 and 2004, among individuals aged 15 years or over, and the Ministry of Health's information system for disease notification (Sistema de Informação de Agravos e Notificação, SINAN) as the information source, the relative risks of AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
3
0
4
Order By: Relevance
“…There are limited data addressing the prevalence and risk factors of MTCT in the western region of the São Paulo State (GONÇALVES et al, 2011). A recent study showed a growing AIDS dissemination among females in small-sized municipalities in the state (PRADO & CASTILHO, 2009). The objective of this study was to determine HIV-1 vertical transmission rates and some characteristics associated with MTCT in a public maternity ward located in the western region of the São Paulo State.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited data addressing the prevalence and risk factors of MTCT in the western region of the São Paulo State (GONÇALVES et al, 2011). A recent study showed a growing AIDS dissemination among females in small-sized municipalities in the state (PRADO & CASTILHO, 2009). The objective of this study was to determine HIV-1 vertical transmission rates and some characteristics associated with MTCT in a public maternity ward located in the western region of the São Paulo State.…”
Section: Introductionmentioning
confidence: 99%
“…Paralelamente, à contínua expansão da epidemia nos epicentros geográficos tradicionais, a epidemia se difundiu por todas as Regiões do país, inclusive, interiorizando-se, conforme observado por (16,17) . O Brasil é um país de dimensões continentais e as diferenças regionais são importantes no que concerne ao perfil da epidemia.…”
Section: Discussionunclassified
“…At the beginning of the epidemic, men were primarily affected; however, AIDS cases have gradually appeared in the female population as a result of unprotected sexual intercourse, contributing to the “feminization” of the disease [10] and resulting in HIV/AIDS prevention public policies that target women beginning in the 1990s [11]. According to Rodrigues-Júnior and Castilho [12], the feminization of AIDS is related to the greater vulnerability of women compared to men, with difficulties in negotiating for protection during intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the most common mode of transmission was also sexual, of which 3.9 % of the respondents were involved in bisexual relationships; the most common age group was those aged 20–39 years. Therefore, the main route of transmission is currently sexual, primarily affecting an age group that tends to be more sexually active [11]. …”
Section: Discussionmentioning
confidence: 99%